Nonspecific chronic low back pain conditions and therapeutic practices in Burkina Faso - Pegdwendé A. Kaboré; Orokiatou B. Zanga; Bénédicte Schepens (AOSIS, 2022)
Background: The management of nonspecific chronic low back pain (NCLBP) is complex because of its multifactorial origin. Objectives: To investigate NCLBP care by evaluating patients' condition and therapeutic management of health practitioners. Method: A cross-sectional survey was carried out among 92 patients with NCLBP, 30 medical practitioners (MP) and 20 physiotherapists (PT) from four public health institutions in Burkina Faso. Patients completed the Visual Analogue Scale, Roland Morris Disability Questionnaire and Fear-Avoidance Beliefs Questionnaire. Practitioners were asked about therapy and continuing professional training. Results: Pain was moderate to intense for 80% of participants with NCLBP. They were functionally affected and showed fear-avoidance beliefs related to physical and work activities. The majority (97%) of medical practitioners prescribed analgesics and 53% prescribed nonsteroidal anti-inflammatory drugs (NSAIDs). Physiotherapy was the most frequently recommended nonpharmacological treatment. Forty-three per cent of medical practitioners referred to physiotherapy; 20% never did. Physiotherapists practised both passive treatments, such as massage (50%), electrotherapy (55%) and thermotherapy (50%), as well as active treatments, such as general exercises (55%), specific exercises (70%), functional revalidation (50%) and back school (40%). Having had recent continuing professional training and assessing risk factors for chronicity were associated with MPs' and PTs' therapeutic choices. Conclusion: Participants with NCLBP showed fear-avoidance beliefs, correlated with their algo-functional status. Prescribing habits of MPs were drug-based. Treatments by PTs were passive and active. Continuing professional training of healthcare practitioners and assessment of risk factors had a positive impact on therapeutic choices. Clinical implications: Our study is an invitation to the health care system to improve the relationship between a patient's NCLBP and therapeutic choices.